Editorial - G. Rizzo; A. Makatsariya (Сеченовский вестник)
A special issue of the Sechenov Medical Journal (No. 2 for 2020) dedicated to COVID-19, attracted great interest within the professional community with a wide range of readers, and opened up the opportunity for a productive discussion of the results obtained by leading Russian experts.